Ответы и объяснения

2013-05-18T17:50:41+00:00

Выражение: D=F+0.25*F+F=0.36*F

Ответ: D-1.25*F-F=0.36*F=0

Решаем по действиям:
1. -F-0.25*F=-1.25*F
2. -1.25*F-F=-2.25*F
3. -2.25*F-0.36*F~~-2.61*F

Решаем по шагам:
1. D-1.25*F-F=0.36*F=0
1.1. -F-0.25*F=-1.25*F
2. D-2.25*F-0.36*F=0=0
2.1. -1.25*F-F=-2.25*F
3. D-2.61*F-0=0=0
3.1. -2.25*F-0.36*F~~-2.61*F

 

Окончательный ответ: D-2.25*F-0.36*F=0=0

По действиям:
1. -1.25*F-F=-2.25*F
2. -2.25*F-0.36*F~~-2.61*F

По шагам:
1. D-2.25*F-0.36*F=0=0
1.1. -1.25*F-F=-2.25*F
2. D-2.61*F-0=0=0
2.1. -2.25*F-0.36*F~~-2.61*F


Решаем уравнение D-1.25*F-F=0.36*F=0: